2021
DOI: 10.7150/ijbs.58427
|View full text |Cite
|
Sign up to set email alerts
|

Livin in synergy with Ras induces and sustains corticosteroid resistance in the airway mucosa

Abstract: Rationale : Corticosteroid resistance (CR) seriously affects the therapeutic effects of steroids on many chronic inflammatory disorders, including airway allergy. The mechanism of CR development is unclear. Recent research indicates that livin, an apoptosis inhibitor, is associated with the regulation in cell activities. This study investigates the role of livin in the inducing and sustaining CR in the airway mucosa. Methods : Nasal epithelial cells (NECs) were isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Interestingly, Xue et al newly discovered that livin played a critical role in ECRSwNP. Livin facilities nasal chronic inflammation by promoting the thymic stromal lymphopoietin (TSLP) expression in nasal epithelial cells [26]. Apparently, it is different with conclusion as described previously.…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, Xue et al newly discovered that livin played a critical role in ECRSwNP. Livin facilities nasal chronic inflammation by promoting the thymic stromal lymphopoietin (TSLP) expression in nasal epithelial cells [26]. Apparently, it is different with conclusion as described previously.…”
Section: Discussionmentioning
confidence: 63%
“…Choi and colleagues revealed that the GC‐resistant group had a higher level of GR‐α than the sensitive group 18 . However, Xue and colleagues observed a decreased GR‐α in the resistant group 16 . Additionally, Li and colleagues reported that the ratio of GR‐α/GR‐β was lower in the GC‐resistant group compared to the sensitive group 17 …”
Section: Resultsmentioning
confidence: 99%
“…18 However, Xue and colleagues observed a decreased GR-α in the resistant group. 16 Additionally, Li and colleagues reported that the ratio of GR-α/GR-β was lower in the GC-resistant group compared to the sensitive group. 17…”
Section: Nasal Polypsmentioning
confidence: 99%
“…Here, we found that upon exposure to PM2.5, RAS activation was enhanced in DCs, which was abolished by the depletion of SOS1, consistent with previous reports ( 13 ). Aberrant RAS activation is one of the factors that skews cellular activities, for example, the uncontrolled growth of cancers ( 13 ), the sustained production of thymic stromal lymphopoietin (TSLP) by airway epithelial cells of patients with allergic rhinitis ( 34 ), and the overexpression of Twist-1 protein in the neutrophils of patients with ulcerative colitis to induce corticosteroid resistance ( 35 ). We observed the increased abundance of TIM4 in the DCs of patients with allergies, as was reported previously ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%